Peningkatan Kapabilitas Guru untuk Mengintegrasikan Creative Thinking dalam Pembelajaran melalui Lesson Study - Elsa Susanti; Nyimas Aisyah; Romi Fajar Tanjung; Hendra Lesmana (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
One of the key skills that students must have in the 21st century is creative thinking. This skill has become a widespread mandate across all sectors of education, industry, and government. The importance of creative thinking skills is not yet in line with the current low level of creative thinking skills among students. One important aspect in developing creativity in learning is the teacher. Through Community Service, lecturers from the Faculty of Teacher Training and Education at Swijaya University provide teachers with knowledge on how to apply creative thinking in learning, improve teachers' skills in developing creative thinking instruments, and improve teachers' skills in applying creative thinking in learning through lesson study. The implementation of community service consists of five stages, namely needs analysis, socialization, training and technology application, mentoring and evaluation, and program sustainability. Through this community service, teachers' knowledge and skills in developing creative thinking instruments have been successfully improved. This improvement resulted in a collection of creative thinking questions from various subjects and, through lesson study, showed a positive influence on improving the quality of learning that supports creative thinking.